Regression model diagnostics (Manning Publications Co., 2021)
Once you've built a regression model, how do you know if it's any good? For linear regression, a standard and often misunderstood diagnostic is the coefficient of determination; for logistic regression, a great diagnostic that should be much more widely known is the coefficient of discrimination. Matthew Rudd, the author of "Regression, a Friendly Guide" talks about both of these measures, what they really mean, and how to use them to make better use of your models.